INNOVATION WORK BEHAVIOR: NEW MODEL TO SUCCESSFUL ORGANIZATION - Sumual, Tineke; Sumual, Shelty; Setyaningsih, Sri; Kalalo, Debie K.R.; Lolong, Rima F.; Koessoy, Herman M. (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This study aims to explore Innovative Work Behavior (IWB) within the educational context, focusing on the contributions of individuals and organizations to the innovation processes within educational institutions. In the face of the complex dynamics heightened by the challenges of the pandemic, the role of innovation has become increasingly crucial to ensure the quality of learning and the achievement of high educational standards. Educators, as primary subjects in this context, are expected to cultivate creative thinking abilities, explore emerging technologies, and advocate for innovative ideas to drive positive change in the education sector. The recent model proposed by Demircioglu et al underscores the critical role of network behavior in shaping IWB, emphasizing the significance of an innovative climate and knowledge sharing as key factors stimulating IWB. The research methodology involves a comprehensive and integrative literature review, providing an in-depth analysis of relevant literature. The study concludes by highlighting the necessity of collaboration among governments, school administrators, educators, educational staff, and the community to create an innovative and responsive educational environment.